Geodetske meritve stabilnosti tal ob tektonskih prelomih na območju Slovenije - Kogoj, Dušan (Geodetski vestnik, 2000)
In the seventies, seismological studies in Slovenia were complemented by geodetic measurements. The measuring instruments, measuring methods and data-processing algorithms employed have enabled conclusions on the stability or nonstability of a specific area in a relative short time periods. Geodetic networks have been set up along tectonic faults and are located in the most interesting parts of Slovene territory. Changes in the positions of network points are determined on the basis of terrestrial measurements performed in selected time intervals. Recently, these standard measurements have been joined and complemented by GPS measurement
Keywords: geodesy; geodezija; geodinamika; geofizika; meritve; stabilnost tal; tektonski prelomi; tektonski premiki